Answer:
Using Faraday's law;
ε= -N ∆ψ(B)/ ∆t;
∆t= -N ∆ψ(B)/ ε
Explanation:
Using Faraday's law; Faraday's law state that the induced emf is directly proportional to the rate of change of time of magnetic flux
ε= -N ∆ψ(B)/ ∆t;
Where ε= induced EMF, ∆ψ(B)/ ∆t is the rate of change of magnetic flux, ψ(B) = BA cos θ
θ= the angle between the magnetic field B and the normal surface area.
We can also calculate the direction of induced magnetic flux. At first, the field is perpendicular to the plane of the loop,the loop can rotate about either an horizontal or vertical axis passing through the mid point